Volatility Analysis of Mutual Funds investment styles in India - Kaur, Saranleen; Bajwa, Rubeena (Gyan Management Journal, 2017)
This study is on analyzing the effect of volatility on the returns of open ended equity mutual Jund investment styles. The empirical methods used for analysis include unit-root tests, GARCH modelling and Granger causality tests. Volatility analysis was done among various investment styles of equity mutual funds viz. large value, large blend, large growth, mid value, mid blend, mid growth, small value, small blend and small growth. The results showed that volatility of large value, large blend, small value and small blend funds was persistent. The Granger causality test was applied to return values for the nine investment styles to analyse the causality among SENSEX and investment styles. The causality test indicated that market returns were independent variable.